Educating for Indigenous public health competence – how do we stack up in Australia?. (28th January 2019) - Coombe, Leanne; Lee, Vanessa; Robinson, Priscilla
Abstract: Objective : Internationally, work is underway to develop or revise public health graduate competencies, of which Indigenous public health competencies are a subset in Australia. This paper outlines the summative results from a review of Master of Public Health (MPH) programs undertaken to determine the level of coverage of Indigenous health in core content and to explore factors that influence the extent of integration. Methods : Of the 22 Australian universities offering an MPH program at the commencement of this study, seven were eventually reviewed using a mixed methods approach. Results : Results showed varying levels of relevant content in both core and elective subjects. Not all reviewed universities taught all the competencies in their core curriculum and some universities did not cover all the competencies in either the core or elective subjects. Conclusion : These findings highlight the need for inclusion of the Indigenous public health competencies to be made obligatory in MPH programs. Implications for public health : Significant gaps remain in public health curricula enabling students to develop competencies that enable them to become judgement safe practitioners when working with Indigenous peoples and communities. A revised curriculum framework document provides a range of useful strategies and resources to remedy these omissions.